The Effect of Serine Protease Inhibitors on Airway Inflammation in a Chronic Allergen-Induced Asthma Mouse Model - Chih-Che Lin; Li-Jen Lin; Shulhn-Der Wang; Chung-Jen Chiang; Yun-Peng Chao; Joseph Lin; Shung-Te Kao (Mediators of Inflammation)
Serine protease inhibitors reportedly attenuated airway inflammation and had antioxidant in multiorgan. However, the effects of the serine protease inhibitors nafamostat mesilate (FUT), gabexate mesilate (FOY), and ulinastatin (UTI) on a long-term challenged mouse model of chronic asthma are unclear. BALB/c mice (6 mice/group) were intratracheally inoculated with five doses of Dermatophagoides pteronyssinus (Der p; 50 μL, 1 mg/mL) at one-week intervals. Therapeutic doses of FUT (0.0625 mg/kg), FOY (20 mg/kg), or UTI (10,000 U/kg) were, respectively, injected intraperitoneally into these mice. Control mice received sterile PBS. At 3 days after the last challenge, mice were sacrificed to assess airway hyperresponsiveness (AHR), remodeling, and inflammation; lung histological features; and cytokine expression profiles. Compared with untreated controls, mice treated with FUT, FOY, and UTI had decreased AHR and goblet cell hyperplasia, decreased eosinophil and neutrophil infiltration, decreased Der p-induced IL-4 levels in serum and IL-5, IL-6, IL-13, and IL-17 levels in bronchoalveolar lavage fluid, and inhibited nuclear factor (NF)-κB activity in lung tissues. The serine protease inhibitors FUT, FOY, and UTI have potential therapeutic benefits for treating asthma by downregulating Th2 cytokines and Th17 cell function and inhibiting NF-κB activation in lung tissue.